Saltwater crocodile and Tomistoma Skeletal and Dental Assessments - Nur Fatimah, Mohd Azizi (Universiti Malaysia Sarawak (UNIMAS), 2017)
In Sarawak, there are two types of crocodiles namely, Crocodylus porosus (saltwater crocodile) and Tomistoma schlegelii (Tomistoma). There were several documentation related to C. porosus skeletal structures, but not for T. schlegelii. Misattribution incidents involving skeletal remains of crocodiles in wildlife forensic field are likely to occur without a proper guideline to be referred to. The aims of this study are to examine and document details on the skull, dentition and other bones of both species. The exhumed skeletal remains were subjected to standard morphological assessment. The structure of C. porosus skull obtained in this study is similar to previous documentation. Tomistoma’s skull has unique taxonomical characters namely the possession of long and narrower snout, D-shaped eye sockets, long and sharp-pointed protruding bones of quaratojugal, straight maxillae and dentary, smooth surface skull, elongated triangle suborbital fenestrae, round shaped internal nares, and the supraoccipital of T. schlegelii is visible from the edge of parietal or from the dorsal view. For teeth arrangement, C. porosus has heterodont dentition, while T. schlegelii has almost approaching homodont dentition. C. porosus has blunt-pointed and irregular size of teet h, whereas T. schlegelii has sharp and similar size teeth. Both taxa showed similar structures of vertebral columns. Additionally, osteoderms of T. schlegelii are relatively larger compare to C. porosus. Information gathered in this study is useful for future forensic identification involving crocodiles in Malaysia.